2020
DOI: 10.1186/s12872-020-01626-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between lipoprotein (a) levels and body mass index in first incident acute myocardial infarction

Abstract: Background: Possible interaction between Lipoprotein (a) (Lp(a)) and body mass index (BMI) was investigated with regard to the risk of first incident acute myocardial infarction (AMI). Methods: Cross-sectional study of 1522 cases with initial AMI and 1691 controls without coronary artery disease (CAD) were retrospectively analyzed using logistic regression model. Subjects were categorized based on Lp(a) and BMI and compared with regard to occurrence of AMI by calculating odds ratios (ORs) with 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Reports of a non-fully explained rise of Lp(a) with diet and exercise exist in literature (10). At the same time, it is found that an interaction with additive effect exists between BMI and Lp(a) in the risk for a first MI (11). In the current study, Lp(a) levels decreased significantly during the follow-up period, while a weak inverse relationship was observed between Lp(a) levels and BMI.…”
Section: Discussionsupporting
confidence: 52%
“…Reports of a non-fully explained rise of Lp(a) with diet and exercise exist in literature (10). At the same time, it is found that an interaction with additive effect exists between BMI and Lp(a) in the risk for a first MI (11). In the current study, Lp(a) levels decreased significantly during the follow-up period, while a weak inverse relationship was observed between Lp(a) levels and BMI.…”
Section: Discussionsupporting
confidence: 52%
“…A cross-sectional study to assess the synergistic effect of Lp (a) and BMI in first incident myocardial infarction reported that elevated Lp (a) concentrations induce a high risk for initial acute myocardial infarction when BMI is elevated. 27 In a research study undertaken to determine the association between Lp (a) levels and high BMI, involving 69,988 individuals, highly elevated Lp (a) levels and high BMI were found to cause a higher risk of calcific aortic valve disease. 28 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Two articles had reported that elevated Lp(a) levels may be associated with AMI in Chinese patients. [40,41] Lp(a) could also act as a biomarker to predict coronary collateral circulation or cardiovascular death in patients with AMI. [42,43] Additionally, Lp(a) interacts with LDL-C in first incident AMI in the Chinese Han population, so that the risk of initial AMI from exposure of elevated Lp(a) combined with elevated LDL-C is much greater than the sum of the risks of each alone.…”
Section: Atherosclerosismentioning
confidence: 99%